Analizar técnica y financieramente la tecnología rigless para intervención a pozo con equipo electro sumergible instalado (2019)
The present work aims to perform the analysis of three rigless technologies implemented in wells with electro-submersible pumping installed as an artificial lift method, for the maintenance or replacement of the pump for the different problems that arise in this survey, such as sandblasting wear or insufficiencies in its parts. To carry out the development, the submersible electropumping and its parts are exposed together with the method currently implemented for this type of work, which is the workover. Giving way to the explanation of each one of the technologies to evaluate ZEiTECS, Redacoil and AccessESP and the Coiled Tubing Slick Line Wire Line maintenance units with which the works applied in the well and through a selection matrix taking into account production deferred labor time availability and security. After selecting the technology that determines the matrix is the best for the case of well Y, we will financially evaluate the application of this defined investment and economic benefits that the installation brings with the traditional processes to define the viability of this through the VPN.